The evaluation of taste sensitivity between conventional and electric smokers - Suhartiningtyas, Dwi; Sofiani, Erma; Rahayu, Dwi Novita; Kumalasari, Mutia; Sa’idah, Haliyati (Odonto : Dental Journal, 2023)
Background: Taste has an important role in human life because of the sense of taste, humans have an ability to taste various flavors of food. Decreased taste sensitivity can affect the quality of life and cause a person to consume excessive taste substances. One of the factors associated with decreased taste sensitivity is smoking. Currently, a new type of cigarette (electric cigarette or e-cigarette) is being developed which is favorable to young people because it has a different content, shape, and taste compared to conventional cigarettes. E-cigarettes are considered safer because aerosol does not contain the tobacco content of conventional cigarettes and is an alternative to smoking cessation programs. The purpose of this study is to evaluate the difference in taste sensitivity between conventional smokers and e-smokers. Method: This research is an analytical observational study using a cross-sectional design. The research subjects were conventional and electric smokers who were students of Universitas Muhammadiyah Yogyakarta. The research subjects were obtained by purposive sampling, a total of 32 people who had met the inclusion criteria. Data analysis used frequency tables for univariate data and an-independent sample T-test for bivariate data. Result: The results of the bivariate analysis showed a significant value between conventional and electric smokers with p = 0.036 (< 0.05) for sweet, salty, and sour tastes, while for bitter tastes p = 0.031 (< 0.05). Conclusion: Taste sensitivity in conventional smokers is less sensitive than in electric smokers. Sensitivity to bitter tastes in both treatment groups is less sensitive than sweet, salty, and sour tastes.